2001
DOI: 10.1211/0022357011775848
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the anxiolytic-like effect of dihydrohonokiol following behavioural and biochemical assessments

Abstract: Previous studies in this laboratory revealed that dihydrohonokiol-B (DHH-B; 3'-(2 propenyl)-5-propyl-(1,1'-biphenyl)-2,4'-diol), a partially reduced derivative of honokiol, was an effective anxiolytic-like agent in mice at an oral dose of 0.04 mg kg(-1), and at higher doses, when evaluated by the elevated plus-maze test. The aim of this study was to further confirm the anxiolytic-like effect of DHH-B using an additional behavioural procedure (Vogel's conflict test in mice) and a biochemical assessment (in-vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Classical benzodiazepines reduce conflict behaviour in rats in the VCT, as measured by an increase in water intake in the presence of shock delivery (Millan and Brocco 2003;Loiseau et al 2003;Griebel et al 1999Griebel et al , 2002Sorbera et al 2001;Flores and Pellon 2000;Nazar et al 1997;Brocco et al 1990). Although similar effects of benzodiazepines have been shown in mice in the VCT, this species has not been routinely used (Liao et al 2003;Maruyama et al 2001;van Gaalen and Steckler 2000;Umezu 1995Umezu , 1999Kuribara et al 1989Kuribara et al , 1990. However, the simplicity of the original VCT in rats and the increased use of transgenic mice in anxiety research (Anagnostopoulos et al 2001) suggest that conditioned mouse models of anxiety are needed to give a more complete picture of the anxiety phenotype of genetically modified mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical benzodiazepines reduce conflict behaviour in rats in the VCT, as measured by an increase in water intake in the presence of shock delivery (Millan and Brocco 2003;Loiseau et al 2003;Griebel et al 1999Griebel et al , 2002Sorbera et al 2001;Flores and Pellon 2000;Nazar et al 1997;Brocco et al 1990). Although similar effects of benzodiazepines have been shown in mice in the VCT, this species has not been routinely used (Liao et al 2003;Maruyama et al 2001;van Gaalen and Steckler 2000;Umezu 1995Umezu , 1999Kuribara et al 1989Kuribara et al , 1990. However, the simplicity of the original VCT in rats and the increased use of transgenic mice in anxiety research (Anagnostopoulos et al 2001) suggest that conditioned mouse models of anxiety are needed to give a more complete picture of the anxiety phenotype of genetically modified mice.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effect of drugs on pain threshold may be difficult to transfer from, for example, the tail-flick test to the VCT context (Millan and Brocco 2003). For these reasons, we have not concentrated exhaustively on obviating all potential confounding variables, although some are inherently addressed by the pharmacological agents tested as well as by previous studies (Liao et al 2003;Maruyama et al 2001;van Gaalen and Steckler 2000;Umezu 1995Umezu , 1999Kuribara et al 1989Kuribara et al , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous pre-treatment or post-treatment of honokiol at a concentration of 0.1 and 1.0 μm/kg significantly decreased the neutrophil infiltration and oxidative damages in the infracted infected brains [24]. It was found that dihydrohonokiol-B [3′-(2 propenyl)-5-propyl-(1,1′-biphenyl)-2,4′-diol], a partially reduced derivative of honokiol, was an effective anxiolytic-like agent in mice at an oral dose of 0.04-1 mg kg −1 [62]. Oral treatment of 0.2 mg/kg honokiol for seven days showed a similar anxiolytic effect with a single treatment of 1 mg kg −1 diazepam in mice [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicated that honokiol possessed the neuroprotective eects, and some of these studies suggest that the amelioration of neurotoxicity by honokiol may be attributed to the anti-oxidative and anti-inammatory actions through, at least in part, limiting lipid peroxidation and reducing neutrophil activation/inltration during ischemia and heatstroke (Sheu et al, 2008;Fukuyama et al, 2002). Laboratory studies also revealed that a partially reduced derivative of honokiol, dihydrohonokiol-B (DHH-B; 3'-(2 propenyl)-5-propyl-(1,1'-biphenyl)-2,4'-diol), was also an effective anxiolytic-like agent in mice (Maruyama et al, 2001). Another possible mechanism for honokiol-mediated neuroprotective effects is thought blockade of glutamate and N-methyl-D-aspartic acid (NMDA) activated excitotoxicity and disruption of ionic homeostasis on various CNS injuries (Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%